2006
DOI: 10.2174/138161206776389840
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Estrogen-Regulated Genes During Development in the Mouse Uterus Exposed to Diethylstilbestrol Neonatally

Abstract: Neonatal diethylstilbestrol (DES) exposure elicits a wide range of abnormalities in the female mouse genital tract. This animal model system is suitable for investigating the mechanism of DES syndrome in humans. Accumulated evidence has shown that critical periods in development are present for distinct and permanent alterations in the female genital tract of mice exposed to DES neonatally (DES-mice). These effects of DES and other estrogens are mainly mediated by estrogen receptor alpha (ER alpha) through mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 98 publications
0
12
0
Order By: Relevance
“…In this regard, an early study demonstrated that application of estrogen to normal hippocampal slices produces a rapid increase in synaptic transmission that is muted in hippocampal slices prepared from male and female ERαKO mice [55]. However, because ERα is critical during development [56] the early ERα knockout mouse cannot be used to separate adult versus developmental effects of ERα. An important recent study in which lentiviral delivery of the gene encoding ERα was delivered to the hippocampus of adult ER-α-knockout (ERαKO) has separated developmental from ERα specific effects on synaptic function and behavior [57].…”
Section: Cognition and Synaptic Plasticity Changes In Er Knockout Modmentioning
confidence: 99%
“…In this regard, an early study demonstrated that application of estrogen to normal hippocampal slices produces a rapid increase in synaptic transmission that is muted in hippocampal slices prepared from male and female ERαKO mice [55]. However, because ERα is critical during development [56] the early ERα knockout mouse cannot be used to separate adult versus developmental effects of ERα. An important recent study in which lentiviral delivery of the gene encoding ERα was delivered to the hippocampus of adult ER-α-knockout (ERαKO) has separated developmental from ERα specific effects on synaptic function and behavior [57].…”
Section: Cognition and Synaptic Plasticity Changes In Er Knockout Modmentioning
confidence: 99%
“…Rodent models have been utilized to evaluate DESinduced infertility, breast cancer susceptibility, reproductive tract abnormalities, and cancer development, as well as investigate the mechanisms involved in disease development later in life. Murine genital tract development at birth is similar to human fetal development at the end of the first trimester (Sato et al, 2004;Yamashita 2006;Ma, 2009). Doses of DES given to pregnant mice or rats varied between 0.2 and 12,000 mg/ day, or approximately 1 mg/kg to 60 mg/kg DES per day in the rat (Hilakivi-Clarke et al, 2013), and these doses were typically oral or via subcutaneous injection in oil.…”
Section: Des Exposure Magnitudementioning
confidence: 88%
“…DES affects the methylation patterns of genes that are associated with proliferation ( c‐jun, c‐fos, c‐myc, ltf ), genes associated with apoptosis ( bcl‐2, bcl‐x ), and growth factors associated with proliferation and differentiation, including epidermal growth factor (EGF) and transforming growth factor (TGF)‐α (Sato et al, ; Newbold, 2006; LeBaron et al, ). This change in methylation is referred to as estrogen imprinting (Yamashita, ). Estrogen imprinting is an epigenetic mechanism where early‐life exposure to estrogens (i.e., DES, Bisphenol A) permanently alters DNA methylation and gene expression of estrogen‐responsive genes.…”
Section: Gene Changes and Proposed Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the paper by Yamashita [7] the current understanding on the molecular basis of diethylstilbestrol-induced uterus anomalies is reviewed. In utero exposure to diethylstilbestrol has been causally linked to clear cell adenocarcinoma of the vagina, breast cancer, and reproductive anomalies.…”
mentioning
confidence: 99%